A complicated case of rhabdomyolysis in dengue fever: finding balance between aggressive hydration and preventing plasma leakage in critical phase - Inche Mat, Liyana Najwa; Mohammad Sallehuddin, Hakimah; Zakariah, Siti Zulaikha; Hoo, Fan Kee; Othman, Ahmad Zaidi (Pakistan Medical Association Rawalpindi Islamabad Branch, 2017)
We present a case of a 43-year-old gentleman presented with dengue shock syndrome following 5 days of fever associated with 2 days of diarrhea. Rhabdomyolysis was diagnosed on the 7th day of illness. He was treated with aggressive hydration and sodium bicarbonate and made an uneventful recovery. The mainstay of treatment is aggresive hydration, with rigorous monitoring of fluid balance. Our case demonstrates the importance of detecting rhabdomyolysis early, as it can worsens the outcome of dengue fever.